Matej Sternen as a restorer - Díaz Fernández, Ivana Nina (Ars et humanitas, 2017)
Matej Sternen (1870-1949) is better known as an impressionist painter rather than for his restoration work, even though in his impressive career he discovered and restored a considerable number of works, especially frescos in Slovenia and Dalmatia (Croatia). His strong interest in restoration can be seen in the numerous notes he wrote about painting technologies, restoration and conservation techniques. This enriched his entire opus, as it stimulated him to try numerous painting techniques and genres, such as frescoes. Sternen was a painter who constructed his paintings very carefully, and a master in the preparation of the painting's surface, or "the ground", and always considered the laws of colours and their relationships and proportions to the white painted surface. In his restoration practice, working together with his close colleagues the art historians France Stele (1886-1972) and Ljubo Karaman (1886-1971), Matej Sternen actualized the principle "conserve instead of restore" that was the rule in his day. This paper is based on fieldwork data and archive sources, kept in Ljubljana, Celje, Split and Zagreb, and focuses on two important monuments - the painted ceiling in the Old Manor House in Celje (Slovenia), and a wall painting in the church of St Michael in Ston (Croatia). These two cases, which are different from both technical and methodological approaches to monument protection, clearly show Sternen's professional expertise and practical realization of "conserve instead of restore", which speaks in favour of preserving the original work as opposed to aggressive restoration interventions.
Keywords: Celjski strop; cerkev Sv. Mihaela v Stonu; Karaman, Ljubo; konservatorstvo; restavratorji; slovenski slikarji; Stele, France; stenske poslikave; Sternen, Matej